Relationship Between Psychological Distress and Irritable Bowel Syndrome (IBS) in Medical Students of Pelita Harapan University - Steven Nanda; Veli Sungono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
Background: Irritable bowel syndrome is a functional disorder with recurrent abdominal discomfort associated with abnormalities in gut motility. One of the risk factors for IBS is anxiety and depression. This study aims to find out the relationship between medical student’s psychosocial conditions, measured by depression and anxiety with incidence of IBS. Gastrointestinal-specific anxiety (GSA), a subset of general anxiety, is measured and its relationship with incidence of IBS is also evaluated.Method: This research is a cross sectional study. Sample consists of 168 medical students from UPH batch 2016-2018 that fits into inclusion and exclusion criteria. Data is collected with demographics questionnaire, Rome IV IBS Criteria, Depression, Anxiety and Stress Scale 21, and Visceral Sensitivity Index. Categorical data between depression and anxiety and IBS is analyzed with Chi Square. GSA is a numerical data and its relationship with IBS is analyzed with t-test. Because GSA All statistical data is analyzed using SPSS version 22.0.Results: Results showed that from 168 samples that are acquired for this research, 65 (38,7%) are IBS and 103 (61,3%) are non-IBS. Significant associations are found between depression (p=0,03), anxiety (p=0,039), gastrointestinal-specific anxiety (p0,001), and obesity (p=0,026) with incidence of IBS.Conclusion: There is a significant association between depression and anxiety with incidence of IBS.